An Analysis of Students’ Anxiety Level in English Oral Performance Viewed from Their Personality - Cipta Riska Nabella, Angelia; Umami, Mashlihatul (Scripta : English Department Journal, 2023)
The aims of the research were to analyze the students’ anxiety levels in English oral performance viewed from their personality and the alternative solutions to overcome students’ anxiety in speaking English at the sixth semester students IAIN Salatiga by using survey methods. To select the participants, the researcher chose students’ randomly, which consisted of 23 pupils to answer two questionnaires from The Foreign Language Classroom Anxiety Scale (FLCAS) and Eysenck Personality Inventory (1959) and interview guidelines[1]. In this research there were three processes for analyzing data, including: data condensation, data display, and drawing conclusion. The implications of this paper are reduced language proficiency, self-esteem, academic performance, impaired fluency and negative attitude towards English. Finally, the result was 1) The anxiety level in speaking was anxiety level of 23 participants is 2 students at a very relaxed anxiety level (9%), 7 students at relaxed anxiety (30%), 11 participants at the level of mild anxiety (48%), 1 person at the anxiety level (4%) and 2 students were very anxious (9%). There are 5 extroverts whose average scales are 1 person is very relaxed, 2 students are at a relaxed level and 2 others are slightly anxious. Meanwhile, there are 18 introverts whose average scale is at a slightly anxious level. 2) The dominant factor in students’ anxiety in speaking English for extroverts are the language factor and stage fear. For introverts, the dominant anxiety factors are peer factors, lack of confidence and shame, past experiences and irrational thoughts.